Technical Aspects and Installation Challenges of Ocean Current Turbines in the Indonesian Strait - Ikram, Andi Muhammad (Collaborate Engineering Daily Book Series, 2025)
The straits of Indonesia possess unique hydrodynamic characteristics resulting from the interaction of tidal currents, the Indonesian Throughflow, and the influence of seasonal monsoons. These conditions make the straits a potential location for the development of turbine-based ocean current power plants. This study discusses the technical aspects and challenges of installing ocean current turbines in Indonesian straits by reviewing key parameters such as current velocity, water depth, seabed characteristics, turbulence, and wave and wind loads. The technical analysis covers the selection of turbine types (horizontal-axis and vertical-axis), foundation systems (monopile, gravity-based, or mooring systems), subsea power transmission systems, and integration into the onshore power grid. The main challenges identified include seasonal current variability, the potential for biofouling and corrosion due to the tropical marine environment, the complexity of installation in waters with strong currents, port infrastructure limitations, and navigation safety aspects in active shipping lanes. Additionally, environmental and social factors such as impacts on marine ecosystems and fishing activities are also important considerations in planning. The study’s findings indicate that, technically, the installation of ocean current turbines in the Indonesian straits is feasible, but requires an adaptive design approach, comprehensive oceanographic studies, and installation strategies that account for local conditions. With proper planning, this technology has the potential to become a reliable and sustainable source of renewable energy for Indonesia’s archipelago.